Alveolar ridge dimensional changes following ridge preservation procedure with novel devices: Part 1 – CBCT linear analysis in non‐human primate model. Issue 1 (6th February 2015) - Min, Seiko; Liu, Yi; Tang, Jianxia; Xie, Yilin; Xiong, Jimin; You, Hyung‐Keun; Zadeh, Homayoun H.
Abstract: Aim: This study sought to investigate dimensional changes to the alveolar bone following extraction and application of novel devices used for obturation of socket orifice (socket cap) and space maintenance in sockets with facial dehiscence (socket cage). Material and methods: Six Macaca fascicularis had six teeth each removed according to the following intervention groups (groups A–C intact alveolar bone; D–E facial dehiscence): negative control (A); socket obturated with cap (B); filled with anorganic bovine bone mineral (ABBM) + socket cap (C); dehiscence negative control (D); socket cap + socket cage (E); ABBM + socket cap + socket cage (F). Serial CBCT scans at preoperatively, 6 and 12 weeks following intervention were compared to quantify linear alveolar bone alterations. Results: Without therapeutic intervention, intact sockets exhibited significant reduction in width at the crestal 2 mm of the ridge crest within 6 weeks. Compared with the negative control sites which lost up to 52% of crestal bone width, sites treated with socket cap + ABBM lost at most 4% of bone width at the crestal 2 mm. Similar results were seen in the dehiscence groups, with the combination of socket cap + socket cage + ABBM maintaining the greatest socket width and height dimensions. Conclusions: Results from the current non‐human primate study suggest that the socket cap and socket cage devices, when used in conjunction with xenograft proved effective in minimizing post‐extraction socket width loss and height seen in both intact sockets and sockets with facial dehiscence defects.